2020
DOI: 10.1159/000510880
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Clinical Features of 1,641 Patients with Alopecia Areata, Alopecia Totalis, and Alopecia Universalis: A Single-Center Retrospective Study

Abstract: <b><i>Background/Aim:</i></b> Alopecia areata (AA) is a common autoimmune hair disorder which is characterized by noncicatricial hair loss. AA commonly presents with localized patches on the scalp and face but may affect any hair-bearing region of the body leading to even more generalized involvement. AA may affect any age group, gender, and race. The current study investigates the demographic characteristics of the patients with AA and subgroups of AA including alopecia totalis (AT) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Approximately 63% of all the incident cases were women, indicating female predominance, as has been observed in previous reports, including a Danish study from 2022 by Andersen et al [ 13 , 31 – 33 ] based on data from the Danish Skin Cohort (based on the DNPR, with dermatologist-verified skin diseases). The proportion of female patients with AA in the current study was slightly lower in the AT/AU subtype (approximately 57%) than in the non-AT/AU subtype (64%).…”
Section: Discussionsupporting
confidence: 61%
“…Approximately 63% of all the incident cases were women, indicating female predominance, as has been observed in previous reports, including a Danish study from 2022 by Andersen et al [ 13 , 31 – 33 ] based on data from the Danish Skin Cohort (based on the DNPR, with dermatologist-verified skin diseases). The proportion of female patients with AA in the current study was slightly lower in the AT/AU subtype (approximately 57%) than in the non-AT/AU subtype (64%).…”
Section: Discussionsupporting
confidence: 61%
“…It can affect any hair-bearing area and varies from patchy diffuse alopecia to universal loss of hair. The global incidence of AA varies from 0.57% to 3.8% in hospital-based studies, and, in general population studies the lifetime incidence of AA varies from 1.7% to 2.1% (2). It is speculated that the variation reflects differences in populations and types of studies (3)(4)(5)(6).…”
mentioning
confidence: 99%
“…15 Additionally, in a US study of 481 Caucasian patients from AA patient conferences, there was a female predominance of AA (female to male ratio 2.3:1), 16 and a Turkish study reported that 53.4% of patients diagnosed as having AA, AT, or AU were female and 46.6% were male. 17 Associations of AA with LGBTQIA+ status, physical disability, socioeconomic status, education level, or health insurance status have not been evaluated in prior epidemiological studies. While LGBTQIA+ status and AA and physical disability were not associated with AA, we found decreased odds of AA in participants without health insurance and those with lower education and lower income.…”
Section: Discussionmentioning
confidence: 99%